CHARACTERISTICS OF A DIFFERENTIATED PHYSICAL TRAINING PROGRAM FOR 12–13-YEAR-OLD ATHLETES IN ITF TAEKWON-DO (Physical Culture and Sport: Scientific Perspective, 2025)
The article addresses a pressing scientific and practical issue—the development of a physical training program based on a differentiated approach. This strategy aims not only to enhance athletes' readiness but also to serve as a foundation for building a long-term, effective training system for qualified athletes. Objective: To characterize the essence of a differentiated physical training program for 12–13-year-old athletes in ITF Taekwon-Do. Methods: Theoretical analysis, synthesis of literature and online resources, pedagogical testing, and methods of mathematical statistics. The methodological foundation of the differentiated approach lies in considering individual indicators of general and specific physical fitness of 12–13-year-old taekwondo athletes. Physical readiness was assessed using ITF Taekwon-Do programmatic and normative guidelines, complemented by recommendations from martial arts specialists. Results: Implementation of the experimental program was enabled through objective grouping of athletes according to priority physical fitness criteria, conducting small-group training sessions, and combining general, auxiliary, and specialized physical training tools. Well-structured workload distribution in accordance with the principles of progression and cyclicity, along with a balanced integration of comprehensive and differentiated components within micro- and mesocycles, created favorable conditions for achieving sustainable training effects. This aligns with modern trends in sports science focused on developing athletic mastery while accounting for each athlete’s individual development pace. Conclusions: The developed differentiated physical training program integrates the comprehensive development of physical qualities with targeted correction of weaker aspects—i.e., the differentiated component of the training process. This approach is intended not only to improve training efficiency but also to lay the groundwork for long-term, purposeful athletic development.
Keywords: training; experimental program; martial arts; content; focus; justification